(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
The research on which this paper is based set out to identify the sexual intercourse euphemisms used in Gĩkũyũ, a Bantu language spoken in Kenya, then discuss the semantic and lexical processes used in those euphemisms, and, finally, point out the specific metaphors that underlie these latter. To achieve these objectives, the research used data collected (using an interview schedule) from 20 native Gĩkũyũ speakers. The euphemisms were assigned to their corresponding semantic and lexical processes, and then discussed in terms of their correspondences between the source domain and target domain, two key concepts of the Conceptual Metaphor Theory. The specific metaphors behind those euphemisms were discussed. It transpired from this discussion that men generally looked at sexual intercourse more as WORK, A GAME, WAR, FOOD and UTILITY, while women looked at it mainly as a form of COMPANIONSHIP.